PceRBase: a database of plant competing endogenous RNA. Issue Volume 45:Issue D1(2017) (7th October 2016) - Yuan, Chunhui; Meng, Xianwen; Li, Xue; Illing, Nicola; Ingle, Robert A.; Wang, Jingjing; Chen, Ming
Abstract: Competition for microRNA (miRNA) binding between RNA molecules has emerged as a novel mechanism for the regulation of eukaryotic gene expression. Competing endogenous RNA (ceRNA) can act as decoys for miRNA binding, thereby forming a ceRNA network by regulating the abundance of other RNA transcripts which share the same or similar microRNA response elements. Although this type of RNA cross talk was first described in Arabidopsis, and was subsequently shown to be active in animal models, there is no database collecting potential ceRNA data for plants. We have developed a P lant ceR NA database (PceRBase, http://bis.zju.edu.cn/pcernadb/index.jsp ) which contains potential ceRNA target-target, and ceRNA target-mimic pairs from 26 plant species. For example, in Arabidopsis lyrata, 311 candidate ceRNAs are identified which could affect 2646 target–miRNA–target interactions. Predicted pairing structure between miRNAs and their target mRNA transcripts, expression levels of ceRNA pairs and associated GO annotations are also stored in the database. A web interface provides convenient browsing and searching for specific genes of interest. Tools are available for the visualization and enrichment analysis of genes in the ceRNA networks. Moreover, users can use PceRBase to predict novel competing mimic-target and target–target interactions from their own data.